Human intestinal parasites on body surfaces of non-biting flies at Universiti Sains Malaysia (USM) Health Campus - Rosly, Norfadzilah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Parasitic infections are major medical problem worldwide. The transmission via nonbiting synanthropic flies has long been recognized but neglected. Therefore, this study aimed to revisit the problem by screening for the presence of human intestinal parasites on body surfaces of flies at Universiti Sains Malaysia (USM) Health Campus. A total of 315 non-biting flies (32 batches) were captured from different sites at Desasiswa Nurani using sweeping net and bottle fly trap. Each batch ( 10 flies per batch) of external body surface of flies was cleansed with 0.9% normal saline by sedimentation method in a 50 ml tube. After removing the flies, the tube was centrifuged to obtain the sediment. A portion of the sediment was observed under a light microscope; other small portions of the sediment were stained with trichrome stain or modified acid-fast stain. Then, the stained slides were screened under a light microscope. The extracted DNA from the sediments was screened for Entamoeba histolytica using duplex PCR assay that amplified SSU-rRNA gene of£. histolytica, in which SSP2 gene of Plasmodium falciparum was incorporated as the internal control to rule out false negative results. The microscopy results showed that 6.3% (2/32) of the fly batches were contaminated with rhabditiform larvae of Strongyloides stercoralis. This result was confirmed by realtime PCR assay. These larvae were obtained from body surfaces of houseflies (Musca domestica) of the Muscidae family. Interestingly, all the sediments from external surfaces of flies were confirmed negative for£. histolytica by duplex PCR assay In conclusion, this study revealed that non-biting flies at Desasiswa Nurani, USM Health Campus are free of almost all common human intestinal parasites. However, these flies are potential transmitter of S. stercoralis infection in the campus.